FRI0342 Measuring Pain Intensity in Older Adults with "Multisite" Peripheral Joint Pain Using a Composite Score. (9th June 2015) - Finney, A.; Dziedzic, K.; Lewis, M.; Ryan, S.; Healey, E.
Abstract : Background: Individuals with peripheral joint pain and osteoarthritis (OA) commonly experience pain in more than one joint site, yet the majority of studies focus on pain at a single site. Pain intensity is the single most assessed dimension in pain assessment. No standardised method of scoring multisite pain intensity as a composite score has been previously developed. Objectives: This study investigated a composite mean pain intensity score for multisite peripheral joint pain (joint pain in two or more sites from the hands, hips, knees and feet) in a community dwelling population of adults aged 45 years and over. Methods: A cross-sectional population survey was mailed to adults aged 45 years and over (n=28, 443) registered with 8 general practices in the North West Midlands, UK as part of the MOSAICS study. Participants provided demographic details and information on the presence and intensity of joint pain in the hands, hips, knees and feet, using a 0-10 numerical ratings scale (NRS).Three methods of generating a mean composite pain intensity score were analysed; i) a mean pain intensity score from each site reported as painful; ii) a mean pain intensity score from all four peripheral sites irrespective of the presence of pain, and iii) the highest reported pain intensity score. Results: Of 15, 083 (53%) respondents, (mean age 63.9 years (11.2sd), 54% female) 11, 928 (79%) reported peripheral joint pain, of whom 11, 813 (99%) provided a pain intensity score. Figure 1 shows mean pain intensity scores for each method stratified by the number of sites of pain. Pain intensity score was associated with an increase in the number of peripheral joint pain sites, irrespective of the way in which the composite score was calculated (figure 1 ). Pain intensity score was also shown to be associated with increasing age, body mass index (BMI) and social deprivation ( p ≤0.001). Pain intensity in a single peripheral joint site increased with the addition of further painful sites. Conclusions: Three different methods used to generate a composite multisite pain intensity score demonstrated associations of pain intensity with increasing numbers of peripheral joint pain sites. Furthermore, mean joint pain intensity increased in single sites with the addition of further painful joint sites. There is currently no standardised approach to measuring multisite pain intensity and the three different approaches offer a range of alternatives. Further work is required to understand the impact of pain intensity in those with multisite peripheral joint pain. Acknowledgements: This research was funded by a National Institute for Health Research (NIHR) Clinical Doctoral Research Fellowship (grant reference: CAT CDRF 10-018). Andrew Finney is part-funded by the National Institute for Health Research (NIHR) Collaborations for Leadership in Applied Health Research and Care West Midlands. The views expressed in this paper are those of the author(s) and not necessarily those of the NHS, the NIHR or the Department of Health. Disclosure of Interest: None declared